Landscape genetics of an early successional specialist in a disturbance‐prone environment. Issue 5 (4th February 2013) - Pereoglou, F.; Lindenmayer, D. B.; MacGregor, C.; Ford, F.; Wood, J.; Banks, S. C.
Abstract Species that specialize in disturbed habitats may have considerably different dispersal strategies than those adapted to more stable environments. However, little is known of the dispersal patterns and population structure of such species. This information is important for conservation because many postfire specialists are at risk from anthropogenic changes to natural disturbance regimes. We used microsatellite markers to assess the effect of landscape variation and recent disturbance history on dispersal by a small mammal species that occupies the early seral stage of vegetation regeneration in burnt environments. We predicted that a postfire specialist would be able to disperse over multiple habitat types (generalist) and not exhibit sex‐biased dispersal, as such strategies should enable effective colonization of spatially and temporally variable habitat. We found significant differentiation between sites that fitted an isolation‐by‐distance pattern and spatial autocorrelation of multilocus genotypes to a distance of 2–3 km. There was no consistent genetic evidence for sex‐biased dispersal. We tested the influence of different habitat‐ and fire‐specific landscape resistance scenarios on genetic distance between individuals and found a significant effect of fire. Our genetic data supported recently burned vegetation having greater conductance for gene flow than unburnt habitat, but variation in habitat quality between vegetation types and occupied patches had no effect on gene flow. Postfire specialists must evolve an effective dispersal ability to move over distances that would ensure access to early successional stage vegetation. Natural disturbance and natural heterogeneity may therefore not influence population genetic structure as negatively as expected.